A Dynamic Approach to the Theory of Effective Demand - Anwar Shaikh (Levy Economics Institute of Bard College, 1989)
This paper attempts to resituate the theory of effective demand within a dynamic nonequilibrium context. Existing theories of effective demand, which derive from the works of Keynes and Kalecki, are generally posed in static equilibrium terms. That is to say, they serve to define a given level of output which corresponds to the equilibrium point between aggregate demand and supply. We propose to generalize this analysis in three ways. First, we will extend the analysis to encompass a dynamic (i.e. moving) short run path of output, rather than a merely static level. Second, we will show that this dynamic short run path need not imply an equilibrium analysis, since it can arise from either stochastically sustained cycles or deterministic limit cycles. And third, we will prove that the preceding generalization of the theory of effective demand will allow us to solve a long standing problem in growth theory: namely, the puzzle surrounding the apparently intractable instability of warranted growth.
Keywords: 330